Analisis Etika Lingkungan Antara Suku Aifat dan Suku Piliang terhadap Etika Lingkungan di Kawasan Unimed - Assyifa'u Qolbiatu Atthoyibah; Gracia Tri Putri Br Ginting; Ivan Fadillah; Mardiana Mardiana; M. Rizky Fauzan Tampubolon; Hanna Mawarni Manullang; Katri Nafisa; Ika Purnamasari (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
In the area of ​​the State University of Medan (Unimed), students from various tribes gather to continue their education. Among them, students from the Aifat and Piliang tribes bring environmental ethics influenced by their geographical and cultural backgrounds. This study uses a qualitative descriptive research method, which was carried out at the State University of Medan (UNIMED) using interview techniques and observations. The data obtained were analyzed using qualitative analysis techniques. The research stage begins with data reduction, data presentation and drawing conclusions. a good understanding of environmental ethics after taking the Basic Social and Cultural Sciences (ISBD) course. ISBD learning has succeeded in enriching students' understanding of the importance of environmental ethics in everyday life, although its application still varies depending on the cultural background of each student.